A review of the subgenus Eudactylocladius (Diptera: Chironomidae) from China - Kong, Fanqing; Sæther, Ole A.; Wang, Xinhua (Zootaxa, 2012)
The subgenus Eudactylocladius Thienemann of the genus Orthocladius van der Wulp from China is reviewed. Three newspecies, O. (E.) brevis, O. (E.) fengensis and O. (E.) intectus are described and illustrated as adult males, and O. (E.) mus-ester Sæther, 2004, O. (E.) priomixtus Sæther, 2004 and O. (E.) subletteorum Cranston, 1999 are recorded from China for the first time and annotated. A key to the Chinese males of the subgenus is presented.